Technical efficiency and spatial externalities: evidence from spanish small and middle-sized industrial firms - Francesc Hernandez-Sancho; Vicent Soler-Marco (European Regional Science Association (ERSA), 2002)
The aim of this paper is to analyze whether firms located inside a hypothetic cluster have a different performance in terms of technical efficiency from firms located outside. To undertake this analysis we present a methodology to overcome the restrictions suffered by this kind of studies, basically the radial efficiency measures. The methodological approach we propose is based on non-radial efficiency measures, also referred as the Russell measure. We present the main results obtained on a sample of small and middle-sized industrial firms located in the Valencian Community (Spain) to show the advantages of this methodology. Furthermore, we assess the links between the spatial location and some management characteristics at firm level.
Keywords: 330